Selective inhibition of methanogenesis by sulfate in enrichment culture with production water from low-temperature oil reservoir. (March 2016) - Lv, Lei; Zhou, Lei; Wang, Li-Ying; Liu, Jin-Feng; Gu, Ji-Dong; Mu, Bo-Zhong; Yang, Shi-Zhong
Abstract: CO2 -reducing, acetoclastic and methylotrophic methanogenesis are three main biochemical pathways for biogenic methane production in subsurface environments. In this study, methanol, formate and acetate were used as substrates amended with low-temperature oilfield production fluid to establish six anaerobic enrichment settings (three with addition of sulfate as exogenous electron acceptor, another three without), incubated at room temperature to monitor the biochemical processes involved in the biodegradation of them. Methane was analyzed in the headspace while acetate, propionate and butyrate were measured in the enrichment cultures during the incubation. Methane was produced in all microcosms regardless of whether sulfate was present or not and stoichiometric estimation indicated that accumulated methane accounted for 44%–76% of the expected in the microcosms without addition of sulfate, while in microcosms with sulfate, 11%–63% of methane was recovered. Methanosarcina and Methanomethylovorans were predominantly detected in enrichment cultures with methanol only, whereas Methanosaeta was the most encounter archaea in microcosms with sulfate and acetate addition. Members represented by Methanomassiliicoccus dominated in both settings amended with formate or methanol when sulfate was present. Our data showed that methanogenesis was selectively inhibited in the presence of sulfate. The high frequency of Methanomassiliicoccus and Methanosaeta in response to sulfate amendement yielded insights into the dynamics of the composition of potential functional microorganisms and also into the metabolic flexibility of methanogens residing in low temperature petroleum reservoirs. These results provide fundamental data on the biochemical process of methane formation, and the shift of methanogenic community through sulfate addition in low temperature oil reservoirs. Highlights: Methanol, formate or acetate methanogenesis was selectively inhibited by sulfate. Methanomassiliicoccus spp. were enriched under sulfate and formate or methanol. Methanosaeta spp. were enriched in acetate/sulfate-dependent microcosms. Methane formation in the presence of sulfate indicates the flexibility of methanogens.